Climbing the Ladder: Hieronymus Bosch and the Vision of Hell - Jacobs, Lynn (The sixteenth century journal, 2021)
Bosch’s paintings are among the best known and most influential images of hell in the history of art. Yet few have noticed an unexpected and unique motif that Bosch repeatedly includes amid the demons, sinners, and burning buildings included within his many depictions of hell: ladders. In the spiritual literature and art of Bosch’s day, the ladder was primarily associated with the concept of spiritual ascent and with the climb to heaven, which explains why no other artists included ladders in their images of hell. The fact that Bosch did so represents one of the many ways in which Bosch upended the artistic traditions of his time. But in addition, it demonstrates how Bosch exploited ambiguity of meaning as a part of his overall strategy of picture-making, and as a way of making his hells even more hellish.